Analysis of luwak coffee volatile by using solid phase microextraction and gas chromatography (Analisa senyawa volatil kopi luwak dengan menggunakan mikroekstrasi fase padat dan kromatolgi gas). - Ariza Budi Tunjung Sari; Teguh Wahyudi; Amrita Sulihkanti (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2012)
The approach to authenticate Luwak coffee is made through analysis of volatile compounds of luwak coffee. Luwak coffee bean from type of arabica obtained from Andungsari Plantation in Bondowoso district, East Java Province Indonesia, was wet processed and sundried prior to roasting step. As many as 120 g green bean was roasted at 170-220°C for 8-12 minutes until reached light brown colour (Agtron scale 65) and was ground prior to extraction. Volatile compounds of roasted Luwak arabica coffee bean were extracted by using solid phase microextraction (SPME) at 60°C for 30 minutes. The extracted analyte was subsequently transferred into GC-FID system by splitless injection at 260°C with five minutes sampling time, continued with separation through 50% phenyl 50% dimethylpolysiloxane capillary column and oven temperature programmed from 60°C to 180°C with rate of 5°C/min. Resulted chromatogram shows major peaks mainly in Rt 8.360-9.981, and Rt 9.705-14.778, and minor peaks identified before Rt 10 and after Rt 24. Varied sample quantity ranged within 0.5-2.5 g produced chromatograms which were not significantly different (p=0.08). This research also observed the use of γ-picoline (4-methylpyridine) as internal standard. It was showed that γ-picoline appeared at Rt 8.6~ without overlaying other peaks originated from sample. Concentration of γ-picoline at 0.05 μL/g, resulted separable peaks. These findings showed that the use of solid phase microextraction and GC-FID is capable to be apply for identification and quantification of Luwak coffee